2010
DOI: 10.1148/radiol.09090304
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Malignant Thrombus from Bland Thrombus of the Portal Vein in Patients with Hepatocellular Carcinoma: Application of Diffusion-weighted MR Imaging

Abstract: DW imaging enables discrimination between bland and neoplastic portal vein thrombi when the ratio of the ADC of the thrombus to the ADC of HCC was lower than 2 and when the thrombi showed similar SI as the primary HCC when qualitative analysis was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 41 publications
6
113
2
5
Order By: Relevance
“…First, restricted diffusion (high signal intensity on diffusion weighted images and decreased ADC values) noted in the splenic and portal veins implied malignant tumor thrombi (6). Second, high signal intensity of tumor thrombus on T1 weighted image was helpful for narrowing the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, restricted diffusion (high signal intensity on diffusion weighted images and decreased ADC values) noted in the splenic and portal veins implied malignant tumor thrombi (6). Second, high signal intensity of tumor thrombus on T1 weighted image was helpful for narrowing the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of PV hemodynamics with 4D flow MRI in a patient with suspected PV thrombosis shows not only a lack of flow in the PV, but also abnormal flow ways in other vessels (15,16). The tumor thrombus may also be differentiated from bland thrombus using diffusion-weighted imaging (DWI); ratio of apparent diffusion coefficient (ADC) of the thrombus to ADC of the primary tumor lower than 2 and similar signal intensity of the thrombus as the primary tumor suggest a tumor thrombus (17). Since DWI does not require contrast use, it can be particularly useful in patients with contraindications to contrast agent.…”
Section: Portal Vein Thrombosismentioning
confidence: 99%
“…Portal vein involvement precludes most curative options [33] , but its diagnosis may be hampered by the presence of a non-neoplastic thrombus in a cirrhotic liver. Few and controversial papers have been published regarding the ability of DWI in distinguishing malignant from non-malignant thrombi: Catalano et al [34] reported that most neoplastic thrombi were isointense to the primary tumor on DWI, whereas all bland thrombi were hypointense; it must be noted that blood degradation products present variable T2 signal prolongation and water diffusivity, therefore false-positives may be encountered at DWI [35] . Satellite nodules are important determinants of patients' prognosis and influence the therapeutic approach.…”
Section: Pancreatic Tumorsmentioning
confidence: 99%